2002
DOI: 10.1051/forest:2002017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle

Abstract: -The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1 . The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 18 publications
(37 reference statements)
6
62
1
5
Order By: Relevance
“…Previous studies concerning the influence of climate on cork growth have concluded that the main climatic factors are: summer drought [6], summer temperatures [6], spring precipitation [37] and autumn-winter precipitations [6,8,9,37]. However, in the present study, climatic attributes were not found to be correlated with cork thickness.…”
Section: Identification Of Variables Influencing Cork Thicknesscontrasting
confidence: 56%
“…Previous studies concerning the influence of climate on cork growth have concluded that the main climatic factors are: summer drought [6], summer temperatures [6], spring precipitation [37] and autumn-winter precipitations [6,8,9,37]. However, in the present study, climatic attributes were not found to be correlated with cork thickness.…”
Section: Identification Of Variables Influencing Cork Thicknesscontrasting
confidence: 56%
“…I valori di accrescimento misurati sono risultati più bassi rispetto a quelli riportati da Natividade (1950) e da Costa et al (2002) per alcune sugherete rispetti vamente dell'area meridionale e centro-occidentale del Portogallo. Per ottimizzare il ciclo di produzione, pertanto, sarebbe auspicabile il prolungamento del turno di decortica.…”
Section: Risultati E Discussioniunclassified
“…L'influenza dei fattori climatici (temperature e pre cipitazioni) sulla crescita del sughero è stata analiz zata mediante l'analisi di correlazione di Pearson (r) fra l'indice di crescita E t e alcuni parametri climatici (Caritat et al 1996, Caritat et al 2000, Martínez 2000, Costa et al 2001, Costa et al 2002, Costa et al 2003, distinguendo i dati per area di produzione.…”
Section: Area DIunclassified
See 1 more Smart Citation
“…L'esperienza parcellare che confronta differenti tecniche di gestione del suolo ribadisce sia l'efficacia degli interventi interfilare e della scerbatura al piede delle piante nell'esaltare la risposta incrementale del legno, sia la capacità della specie di allocare in modo differenziato gli elaborati, destinati in misura maggiore al tessuto suberoso in assenza di interventi colturali; ciò è in linea con quanto riportato da Costa et al (2002) che su piante in produzione, dove solo il 26% dell'incremento annuo è rappresentato dal legno, osservano una relativa costanza di accrescimento del sughero imputata alla minore sensibilità del fellogeno alle variazioni interannuali del regime termopluviometrico. Le relazioni positive tra cure colturali e accrescimento della sughera in fase giovanile sono già segnalate, in ambito regionale, da Abeltino et al (2000) che, in una parcella sperimentale gestita con tecniche colturali intensive comprendenti anche irrigazione di soccorso nei primi tre anni, osservano valori di incremento diametrico, a petto d'uomo e soprascorza, di 6.1 mm anno -1 a fronte dei circa 4 mm registrati in piantagioni condotte con tecniche analoghe a quelle adottate negli imboschimenti galluresi.…”
Section: Discussione Dei Risultati E Conclusioniunclassified